PKN TEACHER'S EFFORT IN THE FORMATION OF STUDENT CHARACTER IN MADRASAH ALIYAH MUALLIMIN UNIVA MEDAN - Gemala Widiyarti (Jurnal Usia Dini, 2017)
"Efforts Teachers Civics In the formation of Student Character at Madrasah Aliyah Muallimin UNIVA Medan". This research is motivated by the low level of character education of learners which become the cause factor of the lack of education of karkter during this time, because the learner is less or still low the character so that the character education needs to be applied to the learner, therefore the duty of the Civic teacher in school is to build and educating students through character education that can nurture the morale of students and practice it in daily life. The formulation of the problem in this research is (1) How is the implementation of Civics teacher in the formation of student character in Madrasah Aliyah Muallimin UNIVA Medan? (2) How is the method applied in terms of character formation of students in Madrasah Aliyah Muallimin UNIVA Medan? (3) What factors inhibit and support the formation of student character in Madrasah Aliyah Muallimin UNIVA Medan? The purpose of this research is to explain the Implementation, Method of Civic teacher in the formation of student character in Madrasah Aliyah Muallimin UNIVA Medan and factor and obstruct and support in the formation of religious character. Research conducted is included in qualitative research. In data collection, the researcher uses participant observation method, Interview and Documentation. Observations were used to obtain data on the implementation of the efforts of Civics teachers in the formation of religious character of students in Madrasah Aliyah Muallimin UNIVA Medan, while the method of interview and documentation used to explore data about methods and factors inhibiting and supporting the formation of religious character of students in Madrasah Aliyah Muallimin UNIVA Medan, and school infrastructure and documents. The results showed that the implementation of Civics teachers in the formation of characters that is by making syllabus and RPP, apply 5S habituation. The method used by the Civic Education teacher is a lecture that relates to the material to be taught, linking with the school's habits. Factors that support the efforts of PKN education teachers in the formation of the character that is the habit of daily behavior in the school, the awareness of students who grew from students to always do a commendable act in life, the existence of each teacher in the formation of the student's religious character, motivation and parental support as well as positive support from the environment. While the inhibiting factor is the social environment (association). The association of students outside the school, the lack of facilities and infrastructure to support the success of Civic teacher strategy in the formation of religious character in the students.Keywords: PKN Learning, Character Education